Características do gênero oral debate a partir de produções orais em oficinas de língua portuguesa - Portes, Evelise Da Silveira (2019)
This Master's dissertation, linked to the Postgraduate Program in Letters, in the area of Linguistic Studies, Federal University of Santa Maria (UFSM), aims to analyze the textual-interactional characteristics of the oral genre debate, from oral productions of students inserted in Basic Education. The theoretical studies that underpin the research are anchored in the notion of language as a form of social interaction, proposed by Bakhtin / Volochinov (2000; 2006); in the socio-interventionist perspective of education, defended by Vygotsky (1993, 2000), as well as in theories related to oral genres (Dolz and Schneuwly, 2004) and to the debate genre (Nascimento, 2015). The research was carried out from the transcripts of two debates produced in workshops of Portuguese Language, stimulated by post-graduate students of the line of research Language and Interaction of UFSM. The analysis of the corpus is based on five criteria presented by Travaglia (2007), namely: the thematic content, the compositional structure, sociocommunicative objectives / function, style and production conditions. With such research, we verified that it is possible to work with orality, and the same oral genre, at different levels of education, through a systematization of the genre. Regarding the textual-interaction characteristics that make up the genre, we find that they are determined by the way the criteria are interconnected in the final configuration of the genre.